2020
DOI: 10.1016/j.ijpam.2019.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent internet addiction - role of parental control and adolescent behaviours

Abstract: Introduction Excessive Internet use can negatively affect academic performance, family relationships and emotional development among the youth. Such issues have been identified as Internet addiction (IA). We aimed to determine the prevalence of IA among Portuguese adolescents and assess how parental control can relate to IA. Methods An observational cross-sectional study was performed at public schools within a Portuguese region, using Young’s Internet Addiction Test su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
2
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 19 publications
7
50
2
7
Order By: Relevance
“…Logistic regression analysis results also indicated adolescent psychiatric patients who had poor relationships with their parents were at significantly higher risk for IAD. This finding converges with other evidence linking IAD with family conflict, an overprotective parenting style, reduced parental supervision, and less family communication ( 58 60 ). Conversely, more harmonious parent-adolescent relationships have positive associations with emotion regulation capacities that serve as a developmental resource that lessens problem behaviors of children ( 61 ).…”
Section: Discussionsupporting
confidence: 90%
“…Logistic regression analysis results also indicated adolescent psychiatric patients who had poor relationships with their parents were at significantly higher risk for IAD. This finding converges with other evidence linking IAD with family conflict, an overprotective parenting style, reduced parental supervision, and less family communication ( 58 60 ). Conversely, more harmonious parent-adolescent relationships have positive associations with emotion regulation capacities that serve as a developmental resource that lessens problem behaviors of children ( 61 ).…”
Section: Discussionsupporting
confidence: 90%
“…This counterintuitive finding may actually reflect a reverse causality, i.e., parents simply engage in more restrictive behaviors after observing their children's addictive use of SNSs. Previous studies showed inconsistent findings where parental restrictive mediation was found to be positively ( 79 , 80 ), negatively ( 41 , 81 ), or insignificantly ( 82 ) related to their children's addictive use of Internet. Researchers have proposed that the association between parental mediation strategies and their children's behavior may be further moderated by other factors ( 37 , 82 84 ).…”
Section: Discussionmentioning
confidence: 88%
“…Specifically, Internet addiction refers to the use of the Internet for non-work activities for more than 6 hr a day for an extended period leading to negative outcomes, such as social withdrawal and poor performance in school or work (Jiang, 2019). Internet addiction poses a risk for the emergence of social and health problems, especially in the form of the potential development of depression, anxiety, lack of real-life social relations, and problems at school and in the family (Jenaro, Flores, G omez-Vela, Gonz alez-Gil, & Caballo, 2007;Martins et al, 2020;Sung, Lee, Noh, Park, & Ahn, 2013). Among a sample of college students, psychiatric symptoms and Internet addiction exhibited bidirectional relationships during a 1-year followup period (Lin, Hsiao, Liu, & Yen, 2020).…”
Section: Internet Addictionmentioning
confidence: 99%